Based nutrition education on Binge Eating Disorder in young adults: Literature review - Laila Rifdiana Dewi (AcTion: Aceh Nutrition Journal, 2026)
Binge Eating Disorder (BED) is one of the most common psychological and social eating disorders worldwide and is recognized as a serious public health problem. One approach to improving BED is mindful eating (ME)-based nutrition education, which helps reduce emotional eating behaviors and improve the quality of food intake. This study aimed to determine the effects and changes obtained from ME-based nutrition education interventions in managing BED among young adults. This study was a narrative literature review. Articles were searched through databases such as Google Scholar, ScienceDirect, ProQuest, and PubMed using the PRISMA flow diagram. The inclusion criteria were experimental studies published between 2019 and 2024. The Joanna Briggs Institute (JBI) checklist was used to assess article quality. Two articles met the selection criteria. The review findings indicate that ME-based nutrition education can reduce the frequency of binge eating and improve eating behaviors. However, because these findings are based on a limited number of studies, generalization should be approached with caution. In conclusion, ME-based nutrition education has the potential to be an effective intervention for managing BED in young adults. Further research with larger sample sizes, rigorous experimental or longitudinal designs, and long-term evaluations is needed to confirm its effectiveness and widespread application.